2019
DOI: 10.1186/s12943-019-1074-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of exosomal PD-L1 in tumor progression and immunotherapy

Abstract: Programmed death ligand 1 (PD-L1), a type I transmembrane protein, binds to its receptor PD-1 to suppress the activation of T cells, thereby maintaining immunological homeostasis. In contrast, tumor cells highly express PD-L1, which binds to receptor PD-1 expressed on activated T cells, leading to immune escape. Anti-PD-1/PD-L1 immune checkpoint therapy blocks the binding of PD-1/PD-L1 to reinvigorate the exhausted T cells, thereby inhibiting tumor growth. Exosomes are biologically active lipid-bilayer nanoves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
234
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(239 citation statements)
references
References 92 publications
(84 reference statements)
4
234
1
Order By: Relevance
“…In this context, it is also noteworthy, that there exists a broad distribution of PD-L1 in different cellular compartments [24]. These formats include not only membranous PD-L1 (mPD-L1) [25], but also cytoplasmic PD-L1 (cPD-L1) [26,27], nuclear PD-L1 (nPD-L1) [28], serum PD-L1 (sPD-L1) [29] and exosomal PD-L1 [30].…”
Section: Characteristics Of the Pd1 Ligands Pd-l1 And Pd-l2mentioning
confidence: 98%
“…In this context, it is also noteworthy, that there exists a broad distribution of PD-L1 in different cellular compartments [24]. These formats include not only membranous PD-L1 (mPD-L1) [25], but also cytoplasmic PD-L1 (cPD-L1) [26,27], nuclear PD-L1 (nPD-L1) [28], serum PD-L1 (sPD-L1) [29] and exosomal PD-L1 [30].…”
Section: Characteristics Of the Pd1 Ligands Pd-l1 And Pd-l2mentioning
confidence: 98%
“…Exosomes from melanoma cells also take part in the immune-escape, either directly inhibiting immune effector cells or indirectly stimulating regulatory cells. The direct modulation of immune cells largely occurs in response to melanoma Exo-related inhibitory or pro-apoptotic signals and are mostly related to the exosomal expression of PD-L1 [32], while the indirect way involves the up-regulation of PD-1 by tumor accessory cells, such as mesenchymal stem cells (MSCs), which engulf the tumor microenvironment and restrain T-cell activation [33]. Moreover, Bland et al have recently discovered an alternative mechanism of melanoma derived-Exo, which affect the epigenetic landscape and mitochondrial respiration of cytotoxic T-cells.…”
Section: Role Of Exo In Melanoma Progressionmentioning
confidence: 99%
“…Immune check point inhibitors target cell surface molecules such as programmed cell death-1 (PD-1) and Programmed cell death-ligand 1 and permit tumor cell killing by tumor-specific CTL. However, recent studies have shown that PD-L1 is often found on exosomes, playing key roles in spreading immunosuppression [76][77][78][79][80][81]. Chemotherapeutics are also reported to be secreted with exosomes.…”
Section: Exosomal Ejection Of Drugsmentioning
confidence: 99%